Arabic Language Academies in Israel Versus the Hebrew Language Academy: between Professionalism and Nationalist Politics. Issue 1 (April 2022) - Amara, Muhammad
Abstract : This article examines the role of Arabic Language Academies compared to the Hebrew Language Academy in the Israeli context. This is a unique context to examine, since we talk about a single academy constructed for the Jewish majority, and multiple academies for the Arab Palestinian minority within the state of Israel. Language academies are established in order to express national identity, constitute a main component in its culture and serve as a factor contributing to modernisation. The study reveals that the work of the Arabic academies is mainly instrumental, focusing on research and the structural aspects of the language, rather than primarily national, as is the case with more established academies. That means the Arabic Academies are professional bodies that deal with the Arabic language. While this is, of course, an important role, it should not be the principal function of the language academies. In contrast, the HLA deals with the structural aspects of the language, corpus planning, and also status planning, as the defender of the Hebrew language, and making the revitalisation of the language possible, combining both professional and national aspects from its inception.